2011
DOI: 10.3389/fmicb.2011.00226
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Actin Pedestal Formation by Enterohemorrhagic Escherichia coli O157:H7 Adapted to the Mammalian Host

Abstract: Upon intestinal colonization, enterohemorrhagic Escherichia coli (EHEC) induces epithelial cells to generate actin “pedestals” beneath bound bacteria, lesions that promote colonization. To induce pedestals, EHEC utilizes a type III secretion system to translocate into the mammalian cell bacterial effectors such as translocated intimin receptor (Tir), which localizes in the mammalian cell membrane and functions as a receptor for the bacterial outer membrane protein intimin. Whereas EHEC triggers efficient pedes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…For example, host-adapted C. rodentium present in the feces of infected mice are in a hyper-infectious state, i.e., highly transmissible and capable of accelerated colonic colonization, compared to C. rodentium grown in LB (Wiles et al, 2005). EHEC grown in gnotobiotic piglets also exhibit enhanced virulence-related phenotypes (Brady et al, 2011). Thus, in considering ways to develop a consistent and predictable CR(ΦStx 2dact ) infection model, we first revisited the preparation of the inoculum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, host-adapted C. rodentium present in the feces of infected mice are in a hyper-infectious state, i.e., highly transmissible and capable of accelerated colonic colonization, compared to C. rodentium grown in LB (Wiles et al, 2005). EHEC grown in gnotobiotic piglets also exhibit enhanced virulence-related phenotypes (Brady et al, 2011). Thus, in considering ways to develop a consistent and predictable CR(ΦStx 2dact ) infection model, we first revisited the preparation of the inoculum.…”
Section: Resultsmentioning
confidence: 99%
“…First, because C. rodentium anaerobiosis is associated with enhanced acid-resistance and a transcriptomic profile more similar that of host-adapted, hyper-infectious bacteria (Smith and Bhagwat, 2013), we changed our culturing procedures by growing inocula without shaking. Studies with other enteric pathogens have revealed that the method of inoculum preparation can have dramatic effects on virulence in animal models (Clark et al, 1998; Brady et al, 2011). Second, we infected mice by feeding to avoid potential physical trauma.…”
Section: Discussionmentioning
confidence: 99%
“…This enhancement of receptor function by pedestal formation increases overall translocation by increasing bacterial attachment but does not result in enhancement of type III translocation by each bacterium. Upon adaptation to the mammalian host, EHEC translocation of pedestal-promoting (and presumably other T3) effectors into mammalian cells is greatly enhanced per bound bacterium (55). Hence, it will be of interest to investigate the mechanism by which actin pedestal formation promotes bacterial attachment, as well as the (unknown) factors that control the efficiency of EHEC type III translocation.…”
Section: Figmentioning
confidence: 99%
“…Acute phase proteins associated with innate immune response to infection are often used to distinguish between bacterial and viral infections in swine veterinary practice as done in human medicine (H. Murata, Shimada, and Yoshioka 2004). Swine present symptoms characteristic of human infections and are susceptible to many enteric human pathogens (Andrutis et al 2000;Brady et al 2011;Jeong et al 2010;Sheoran et al 2012;Steele et al 2010;Widmer et al 2000;Yuan et al 1996). Swine are routinely used for studies of infections that burden human populations (Rajao and Vincent 2015) and for developing antibodies and vaccines (Sandbulte et al 2014).…”
Section: Immune Systemmentioning
confidence: 99%